Micro-organismos associados à Apis mellifera e bioprospecção de componentes da imunidade da abelha - Denise de Oliveira Scoaris (2014)
The bees are the most abundant group of Hymenoptera. In the Apis genus, A. mellifera is the most representative species. The immune system in Apis comprises both individual and social mechanisms. Among the social immunity, propolis is recognized as an important component, given its antimicrobial activity. The microbiota associated with this insect can also be considered a mechanism of immunity, since it can help the host against pathogens. The aims of this study were to evaluate the role of propolis on the immune response in A. mellifera, by the evaluation of immune gene expression; and the survey of the microbial diversity in A. mellifera substrates, both in Brazil and in the United States. A. mellifera were challenged with representative microorganisms (Staphylococcus aureus, Escherichia coli and Candida albicans) and saline, and were incubated in the presence or absence of propolis. In the United States, the seasonal effect between winter and summer was also evaluated. Bioprospection of A. mellifera immune components was accessed through the expression of antimicrobial peptides genes (Hymenopatecina, Abaecina, Apidaecina and Defensin 1), cell recognition protein (AmEater) and storage protein (Vitellogenin). To evaluate the microbiota associated with A. mellifera, the following substrates were surveyed: corbicular pollen, bee bread, nurse and foragers bees surface, hive debris and intestinal contents. It was observed that bees challenged with microorganisms suspensions did not have a higher AMP expression than those inoculated with saline, indicating a significant but not specific immune response. The propolis appears to modulate the immune response, clearly in unchallenged American bees: in the winter, the exposure of control bees to the propolis was able to decrease the expression of Hym in all hives, Aba in three hives and Api and Def1in two hives, compared to control groups not exposed to propolis. The substrates with higher species richness were the hive debris in Brazil and surface of foragers bees in the United States. A total of 214 yeasts isolates were retrieved, 84 from Brazil and 131 from the United States, comprising 45 taxa. The most prevalent yeast species was Aureobasidium pullulans, followed by Candida and Rhodotorula species. Only 6 yeast species were common to both environments. For bacteria, 283 isolates were retrieved, 125 from Brazil and 158 from the United States, accounting for 61 taxa. A total of 71 isolates (25%) was identified as acid lactic bacteria. Most bacterial isolates belonged to Bacillus genus, from Firmicutes Phylum. Among the lactic acid bacteria, the genus Lactobacillus were the prevalent. Only 12 out 61 bacterial species were common in both environments. Two new species, one yeast and one bacterium were observed in association with A. mellifera. These results suggest that bees of the same species have their microbiota composed largely of microbial species present in the foraging environment, which reflects the distinct yeasts and bacteria communities between the two environments.